How energy consumption is related to agricultural growth and export: An econometric analysis on Iranian data - Ahmad Ali Ghaseminejad Raeeni; Safdar Hosseini; Reza Moghaddasi (Energy Reports, 2019)
Iranian agriculture has been supported by cheap energy for decades. So the question of whether this policy had brought any real outcome in terms of sector growth and export is of high importance for policy making. This paper tries to empirically identify such relation by using time series econometrics techniques including causality and cointegration tests for the period 1967-2015. Main results confirm existence of a unidirectional causality from energy consumption to agricultural growth while no relation is found between energy consumption and export. Other findings revealed that one percent increase in energy use results in 1.29 percent rise in agricultural growth in the long-run. In order to avoid detrimental impacts on sector growth, gradual liberalization of energy price for agricultural uses is recommended.
Keywords: 330; Agricultural export; Agricultural growth; Energy consumption; Iran